1993
DOI: 10.1002/ppul.1950150103
|View full text |Cite
|
Sign up to set email alerts
|

Lung recoil and the determination of airflow limitation in cystic fibrosis and asthma

Abstract: A reduction of lung recoil pressure could aggravate any airflow limitation that might be present in patients with cystic fibrosis (CF) or asthma. In a group of 22 children and young adults (8 with cystic fibrosis, 8 with asymptomatic asthma, and 6 healthy controls) aged 8-24 years, lung recoil pressure (Pst) at 100%, 90%, and 60% of TLC and static lung compliance (Cst) were measured using an esophageal balloon. The indices of airflow limitation, including maximal expiratory flow at 25% VC (Vmax25), forced expi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Lung elastic recoil, airway conductance, and airway collapsibility are all important in the pathogenesis of airflow obstruction. Loss of lung elastic recoil pressure results in a reduction of the driving force to generate airflow, and is thought to decrease airway conductance secondary to a loss of the tethering forces that distend the airways [1,2,23]. Airflow obstruction correlated significantly with loss of lung elastic recoil pressure in the group of patients studied.…”
Section: Airflow Obstruction In Relation To Lung Elastic Recoil Airwmentioning
confidence: 80%
See 1 more Smart Citation
“…Lung elastic recoil, airway conductance, and airway collapsibility are all important in the pathogenesis of airflow obstruction. Loss of lung elastic recoil pressure results in a reduction of the driving force to generate airflow, and is thought to decrease airway conductance secondary to a loss of the tethering forces that distend the airways [1,2,23]. Airflow obstruction correlated significantly with loss of lung elastic recoil pressure in the group of patients studied.…”
Section: Airflow Obstruction In Relation To Lung Elastic Recoil Airwmentioning
confidence: 80%
“…Maximal expiratory flow in COPD could be reduced by three different mechanisms. Firstly, loss of lung elastic recoil can decrease the driving pressure [1,2]. Secondly, inflammatory thickening and narrowing of airways can decrease the airway conductance upstream of flow-limiting segments.…”
mentioning
confidence: 99%
“…Previous investigations have demonstrated that pulmonary hyperinflation influences lung mechanics in terms of increased work of breathing, greater severity of breathlessness, impaired respiratory muscle function [53-58] and increased energy expenditure and oxygen consumption [55,56,59]. Recognition of functional deterioration is therefore critical to the ongoing management of patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in asthmatic subjects, RV is determined by airway closure and, hence, it may be affected by increased airway stability that should accompany the increase in Pel,L during Manoeuvre No. 3 [20,21]. It has been shown that patients with emphysema have extensive collateral ventilation, which helps to preserve gas exchange [22].…”
Section: Discussionmentioning
confidence: 99%